2019
DOI: 10.1016/j.concog.2019.102767
|View full text |Cite
|
Sign up to set email alerts
|

The role of levels of processing in disentangling the ERP signatures of conscious visual processing

Abstract: Highlights • We manipulated the level of processing of colored digits in a backward masking task with constant stimulus parameters • ERP results suggest the existence of temporal unfolding of ERP markers of conscious processing • Both early and late components of the ERP response may correspond to neural activity involved in representing conscious content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 55 publications
4
41
2
Order By: Relevance
“…Evidence from other paradigms (visual masking or lowcontrast stimuli) that have recorded electrophysiological measures (EEG or MEG) in combination with visibility/awareness ratings also report modulations during the VAN time range in connection to reported visibility (Andersen et al, 2016;Derda et al, 2019;Koivisto & Grassini, 2016;Tagliabue et al, 2016). Although P3/LP modulations were observed in these studies as well, they were not found as consistently (e.g., only for a high-level but not low-level condition in Derda et al, 2019) and were less predictive of the visual impression (Andersen et al, 2016;Koivisto & Grassini, 2016) as compared to the VAN.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from other paradigms (visual masking or lowcontrast stimuli) that have recorded electrophysiological measures (EEG or MEG) in combination with visibility/awareness ratings also report modulations during the VAN time range in connection to reported visibility (Andersen et al, 2016;Derda et al, 2019;Koivisto & Grassini, 2016;Tagliabue et al, 2016). Although P3/LP modulations were observed in these studies as well, they were not found as consistently (e.g., only for a high-level but not low-level condition in Derda et al, 2019) and were less predictive of the visual impression (Andersen et al, 2016;Koivisto & Grassini, 2016) as compared to the VAN.…”
Section: Discussionmentioning
confidence: 99%
“…According to this point of view, VAN would reflect a pre-conscious stage. Besides, others pointed out a twofold contribution of VAN and LP in triggering perceptual experience (Rutiku et al, 2015 , 2016 ; Tagliabue et al, 2016 ; Derda et al, 2019 ; Ye et al, 2019 ). Our approach has the added benefit of going beyond these findings, dissociating the processes that are not directly related to awareness and may act as confounds.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results challenge the idea that the P3b is a neural signature of conscious processing. While this particular neural activation pattern has been widely replicated and continues to be systematically put forth as a possible neural signature of consciousness (Railo et al, 2010;Dehaene, 2014;Naccache, 2018;Ye et al, 2019;Derda et al, 2019), these prior studies always had participants report their experiences. Although it may be the case that the theoretical foundation supporting those prior studies may ultimately be proven correct (i.e., cognitive/higher-order theories), these results conclusively demonstrate that the P3b is not a signature of conscious processing.…”
Section: Resultsmentioning
confidence: 95%
“…We focused on arguably the largest and most replicable piece of neural evidence cited by cognitive theories: the P3b event-related potential (ERP). While numerous signatures of conscious processing have been proposed (i.e., an "ignition" of fronto-parietal circuits, an increase in long-range neural synchrony, and a late burst of gamma-band oscillations, Dehaene, 2014), the P3b has been widely replicated and continues to be routinely cited as a neural marker of conscious experience (Railo et al, 2011;Naccache, 2018;Ye et al, 2019;Derda et al, 2019).…”
Section: Introductionmentioning
confidence: 99%